THE PREDICTED QUALITY ADJUSTED LIFE YEARS (QALYs) USING ST. GEORGE RESPIRATORY QUESTIONNAIRE (SGRQ) IN INDONESIAN TUBERCULOSIS PATIENTS - Dyah Aryani Perwitasari (Journal of Global Pharma Technology, 2017)
Tuberculosis (TB) disease is one of the chronic diseases which could influence the patients’ quality and quantity of life. The quality and quantity of life may be affected by the disease itself or the disease’s treatment due to the adverse effect. The purpose of this research is to predict Quality Adjusted Life Years (QALYs) value before and during the treatment using Indonesian version of St George Respiratory Questionnaire (SGRQ) instruments which has been validated. This study used a cross sectional design conducted prospectively in 91 new patients diagnosed as pulmonary TB in Pulmonary Clinics, Province of Yogyakarta on November 2013 until April 2015. Patients filled out the SGRQ and the total score was counted  to predict the QALYs.We found that the predicted QALYs before and during the treatment significantly different with value was 0,691 before the treatment and they were 0.805; 0.846; 0.877; 0.892 and 0.899 during the first until fifth month of treatment respectively (p<0,05). The TB treatment can improve health status from index number 0.691 to 0.899 which is 0.208 during the treatment will produce 2 QALYs.  We conclude that the predicted QALYs of TB patients during the treatment are good and show that the patients experience significant improvement of quality of life.